Anthracene-Fused Oligo-BODIPYs: A New Class of π-Extended NIR-Absorbing Materials - Labella, Jorge; Durán-Sampedro, Gonzalo; Krishna, Swathi; Martínez-Díaz, M. Victoria; Guldi, Dirk Michael; Torres, Tomás (Angewandte Chemie International Edition, 2022)
Large π-conjugated systems are key in the area of molecular materials. Herein, we prepare via AuI-catalyzed cyclization a series of fully π-conjugated anthracene-fused oligo-BODIPYs. Their structural and optoelectronic properties were studied by several techniques, ranging from X-ray, UV/Vis, and cyclic voltammetry to transient absorption spectroscopy. As a complement, their electronic structures were explored by means of Density Functional Theory (DFT) calculations. Depending on the size and shape of the π-conjugated skeleton, unique features—such as face-to-face supramolecular organization, NIR absorption and fluorescence as well as strong electron accepting character—were noted. All in all, the aforementioned features render them valuable for technological applications.
CRIS-Team Scopus Importer:2022-12-23
Keywords: BODIPY; Conjugation; Dyes/Pigments; NIR; π-Systems